MODEL PEMBELAJARAN DISCOVERY LEARNING UNTUK MENINGKATKAN KEMAMPUAN PENALARAN MATEMATIS PESERTA DIDIK - Amukti Taraka Bima (Jurnal Edukasi dan Penelitian Matematika, 2020)
Mathematical reasoning_is an ability that must be possessed bystudents today becauseit will train students' ability to reason and think critically. Low mathematical reasoning skills because learning in schools is not optimal. The application of learning models discovery learning can improve mathematical reasoning skills. The purpose of this study is to describe theoretically whether discovery learning can improve mathematical reasoning. This type of research is a study of literature where data collection is done by tracing sources related to the topics discussed both from textbooks, journals and other sources. The conclusion of this literature study is theoretically a discovery learning model that can improve mathematical reasoning ability which can be seen from the achievement of mathematical reasoning indicators.Keywords __ Discovery Learning, Mathematical Reasoning